2004
DOI: 10.1189/jlb.1203641
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin-12 gene expression and its anti-tumor activities by prostaglandin E2 derived from mammary carcinomas

Abstract: Interleukin-12 (IL-12)-mediated immune responses are critical for the control of malignant development. Tumors can actively resist detrimental immunity of the host via many routes. Prostaglandin E 2 (PGE 2 ) is one of the major immune-suppressive factors derived from many types of tumors. Here, we show that systemic administration of recombinant IL-12 could therapeutically control the growth of aggressive TS/A and 4T1 mouse mammary carcinomas. However, PGE 2 produced by tumors potently inhibits the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 74 publications
4
32
0
1
Order By: Relevance
“…First, macrophages from c-fos knockout mice produced significantly more IL-12p70 as compared with macrophages from wild type mice (41). Second, transfection of RAW264.7 cells with a dominant-negative mutant of AP-1 dramatically enhanced IL-12p40 production (40). Our findings are further supported by a recent study showing that histamine enhances AP-1 DNA binding in keratinocytes (42).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…First, macrophages from c-fos knockout mice produced significantly more IL-12p70 as compared with macrophages from wild type mice (41). Second, transfection of RAW264.7 cells with a dominant-negative mutant of AP-1 dramatically enhanced IL-12p40 production (40). Our findings are further supported by a recent study showing that histamine enhances AP-1 DNA binding in keratinocytes (42).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, we conclude that H4R signaling is able to induce the transcription factor AP-1 without phosphorylation of ERK1/2. AP-1, a heterodimer consisting of c-Fos and c-Jun, is a downstream target for MAPK pathways, i.e., ERK1/2, JNK, and p38 MAPK (40). AP-1 activation has been previously related to the inhibition of IL-12p70 in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although PGE2 is proinflammatory, it is usually thought to have immunosuppressive effects 78 . PGE2 levels were attenuated in cells that were coincubated with the COX2 inhibitor NS-398.…”
Section: Cox2 and Prostaglandin Synthesismentioning
confidence: 99%
“…For example, macrophage expression of IL-12, a cytokine known to stimulate both the proliferation and cytotoxicity of T cells and NK cells (60), is markedly suppressed in tumors, possibly by exposure to IL-10, PGE 2 , and TGF-h1 (8,61). By coinjecting mice with human prostate tumor cells and macrophages engineered to overexpress IL-12, Satoh et al (62) showed that it was possible to quickly reestablish enhanced expression of MHC in TAMs along with increased T-cell infiltration and an antitumor immune response, resulting in a marked reduction in the growth of both the primary tumor and lung metastases.…”
Section: Roles Of Tam In Tumor Progressionmentioning
confidence: 99%